The role of TRPV1 in RA pathogenesis: worthy of attention - Qu, Yuan; Fu, Yang; Liu, Yuan; Liu, Chuanguo; Xu, Bing; Zhang, Qian; Jiang, Ping (Frontiers in Immunology, 2023)
Transient receptor potential cation channel subfamily V member 1 (TRPV1) is a Ca 2+ permeable, non-selective cation channel that is found primarily in sensory nerve fibres. Previous studies focused on pain transmission. However, recent studies have found that the TRPV1 channel, in addition to being associated with pain, also plays a role in immune regulation and their dysregulation frequently affects the development of rheumatoid arthritis (RA). A thorough understanding of the mechanism will facilitate the design of new TRPV1-targeted drugs and improve the clinical efficacy of RA. Here, we provide an updated and comprehensive overview of how the TRPV1 channel intrinsically regulates neuronal and immune cells, and how alterations in the TRPV1 channel in synoviocytes or chondrocytes extrinsically affect angiogenesis and bone destruction. Rapid progress has been made in research targeting TRPV1 for the treatment of inflammatory arthritis, but there is still much-uncharted territory regarding the therapeutic role of RA. We present a strategy for targeting the TRPV1 channel in RA therapy, summarising the difficulties and promising advances in current research, with the aim of better understanding the role of the TRPV1 channel in RA pathology, which could accelerate the development of TRPV1-targeted modulators for the design and development of more effective RA therapies.